Analisis Implementasi Strategi Pemasaran Islami Pada Produk Tabungan Emas Dalam Menarik Minat Nasabah Di Bank Syariah Indonesia Kcp. Buleleng - Rafik, Zainur; Handayani, I Gusti Ayu Anisa (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2023)
The growing development of financial institutions, both banks and non-banks in Indonesia, will encourage financial institutions to always maximize their marketing activities. Indonesian Sharia Bank KCP. Buleleng has several superior products, one of which is gold savings. The focus of this research is 1) Implementation of Islamic marketing strategies for gold savings products in attracting customer interest at Bank Syariah Indonesia KCP. Buleleng, 2) supporting and inhibiting factors for implementing Islamic marketing strategies for gold savings products in attracting customer interest at Bank Syariah Indonesia KCP. Buleleng. The research method used is qualitative research which is a field. The data collected includes primary data and secondary data. Sources of data obtained through observation, interviews, and documentation. The analysis technique used is through data reduction, data models, and conclusions. The results of this study indicate that Bank Syariah Indonesia KCP. Buleleng has implemented elements of an Islamic marketing strategy, namely segmentation, targeting, positioning, marketing mix through promotion. And in marketing, it is based on the characteristics of Islamic marketing, namely, theistic (rabbaniyah), ethical (akhlakiyyah), realistic (al-waqiyyah), and humanistic (al-insanniyah). The supporting factor above is the presence of competent employees. The inhibiting factors are the lack of public knowledge about gold savings and the existence of other rival agencies.